TEACHING SPEAKING USING SIMULATION TO THE EIGHT GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Cintya Ayodya Prabowo; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2018)
Simulation means simulate a real life activity.The objectives of this research are to describe a) how the implementation of simulation in teaching speaking skill and b) the strengths and weaknesses towards the implementation of simulation technique in teaching speaking to the eighth grade students of SMPN 1 TlogomulyoTemanggung. This study was action research where the main data were in the form of descriptive qualitative by conducting classroom observation and interview. The results of the research showed that the implementation of simulation in the teaching and learning process of speaking was improving the students’ motivation. They were more enthusiastic in learning speaking and the students were interested in speaking activities. Besides, the researcher found some strengths and weaknesses in implementation simulation technique. The strengths were the students motivated and have effective aspects in social interaction. Meanwhile, the weaknesses of the simulation were the activities artificial and difficult to monitor.